Demographic and Aetiological Outline of Patients Requiring Low Vision Aids in a Tertiary Care Hospital in Rural Eastern India - Saha, Indranil; Singh, Anubhav (Nepalese Journal of Ophthalmology, 2024)
Introduction: Patients with low vision and functional blindness have been increasing. Low vision aids (LVA) are devices or tools that help individuals with visual impairments to enhance their existing vision and maintain physical independence. Understanding demographic profile is crucial to tailor interventions and services to meet their specific needs. Objective: To assess demographic and aetiological profile of patients attending low vision clinic at a tertiary grade teaching eye hospital. Methodology: This retrospective, non-interventional study was conducted in a tertiary grade teaching eye hospital. All patients (census) attending LVA clinic between 2022 April 12 and 2023 April 12 were included. Patient data were collected through evaluation of registered patient records after institutional ethical committee approval. Result: Majority of LVA clinic patients were males (64.77%), with ages from 11-20 years (25.15%). Posterior segment pathologies (87.42%) were more common than anterior (12.57%). The overall common causes of low vision were: retinitis pigmentosa (10.06%), retinochoroidal coloboma (7.54%), macular scar (5.66%). In males, posterior segment involvement was 86.40%; retinal causes 82.02% and optic nerve: 17.97%; common vitreoretinal causes were retinochoroidal coloboma (20.54%), macular scar (12.32%), retinitis pigmentosa (12.32%); common optic nerve causes were primary optic atrophy (12.5%), secondary optic atrophy (87.5%); and common corneal causes: microphthalmos (42.85%), leucomatous corneal opacity (7.14%), anterior staphyloma (7.14%). In females, posterior segment involvement was seen in 83.92%, retinal causes 80.85%, optic nerve 19.14%; the common vitreoretinal causes were retinitis pigmentosa (26.31%), macular scar (13.15%), HMD (10.52%); common optic nerve causes were primary optic atrophy (33.33%), secondary optic atrophy (66.66%), and common corneal causes: Leucomatous corneal opacity (33.3%), microphthalmos (22.2%), microcornea (22.2%). Conclusion: The LVAs are essential tools to provide functional vision to those with severely compromised vision. Better awareness and understanding of this visual rehabilitation are vital to individualise treatment for such patients to help enhance quality of life.